FREQUENCY OF POSTOPERATIVE COMPLICATION IN PATIENT UNDERGOING HEMI-THYROIDECTOMY WITH AND WITHOUT DRAIN (Journal of Medical & Health Sciences Review, 2025)
Introduction: After thyroid surgery, the need for drain placement has become a contentious topic. Drains are frequently utilized to prevent problems and help in the early detection of postoperative bleeding. Bleeding following thyroid surgery is rare, but it can be fatal and requires immediate reoperation. Therefore, many surgeons utilize drains even after basic thyroid surgery. The purpose of this study was to compare the mean pain score and frequency of postoperative complication in patient undergoing hemi-thyroidectomy with and without drain.Materials & Methods: This randomized controlled study was conducted on 100 patients (50 in each group) of age 20-50 years with single or multiple nodules in one lobe undergoing hemi-thyroidectomy. Individuals with a history of bleeding problems, systemic conditions such as diabetes and hypertension, toxic goiter involving both lobes, and thyroid cancer were not included. Using the lottery method, patients were split into two groups at random. Hemi thyroidectomy without drain was performed on patients in group A, and hemi thyroidectomy with drain was performed on patients in group B. The patients' postoperative problems (pain, hematoma, seroma, and wound infection) were monitored for 30 days. Results: In my study the mean post-operative pain was 1.94 ± 0.91 for no drain group versus 3.90 ± 0.97 for drain group (p-value = 0.0001) as shown in Table II. Results showed no (0%) hematoma cases, 00 (0.0%) seroma, wound infection in 01 (2.0%) in group A whereas 01 (2.0%) hematoma, 02 (4.0%) seroma, 04 (8.0%) wound infection in group B with p-value greater than 0.05.Conclusion: This study concluded that in terms of mean pain score and complication rate, the hemi-thyroidectomy without drain installation is superior than the hemi-thyroidectomy with drain placement.